Manual clock distribution technique in partitioning stage for multi-FPGA prototyping - Salahuddin Savugathali; Muslim Mustapa; Fazrul Faiz Zakaria (Institute of Advanced Engineering and Science, 2019)
As the complexity of ASIC/SoC design is increasing along with the number of logic gates, a prototyping process in the verification stage is facing a challenge when the ASIC/SoC design cannot fit into a single FPGA. A solution to prototyping multi-million logic gates of ASIC/SoC circuit into the FPGA platform for verification purpose is by partition the design into multi-FPGA. There are various implementation tools and platform available in the market which automates an FPGA-based prototype phase such as Cadence Protium Rapid Prototyping Platform, Synopsys and S2C. In this paper, Synopsys protocompiler tool will be used to perform the prototyping process of the large 4 core CPU based circuit into the HAPS-80 FPGA platform. This paper will be focusing on the partition requirement needed to successfully prototype the large SoC circuit into the multi-FPGA. The presence of cut clocks in a circuit after partition stage will resulting to the failure in routing stage due to the congestion error. In this paper, two techniques are used, which is automatic clock replication by the Synopsys Protocompiler tool and our proposed technique which is Manual Clock Distribution technique to solve the presence of the cut clock, so that the circuit is able to meet the partition requirement to complete the prototyping process into multi-FPGA. Obtained result from the proposed technique showing that prototyping the large SoC circuit into the multi-FPGA platform has met the specification by eliminating 100% presence of cut clock.